Optimalisasi Pengelolaan Data Vendor Menjadi Dashboard Interaktif Menggunakan Google Data Studio di PT LEN Industri (Persero) - Adam Husain; Siti Nurhayati (Universitas Kebangsaan Republik Indonesia, 2024)
The manual management of vendor data at PT Len Industri (Persero) has led to limitations in access and operational efficiency. To address these challenges, an interactive dashboard utilizing Google Data Studio was developed as a digitalization solution, enabling a more systematic data visualization, real-time access, and enhanced transparency.The implementation results indicate that the dashboard accelerates data retrieval processes, provides visually comprehensible displays, and improves management decision-making efficiency. Furthermore, the automation features help minimize errors in data management and enhance operational accountability. Thus, the use of an interactive dashboard has proven to be effective in optimizing vendor data management and supporting improved company operational performance.